2010
DOI: 10.1080/02786826.2010.488256
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Inhaled Ultrafine Aerosols in Replicas of Nasal Airways of Infants

Abstract: Experimentally measured deposition of ultrafine particles, ranging from 13-100 nm in diameter, in nasal airway replicas of ten infants aged 3-18 months is presented. The replicas included the face, nostrils, and nasal airways including the upper trachea. A differential mobility analyzer (DMA) and a condensation particle counter (CPC) were used to quantify the nasal deposition by comparing the number of polydisperse sodium chloride particles, generated by evaporation from a Collison atomizer, at the inlet and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A similar work to use such a high-resolution mesh is that of Doorly et al (2008). Earlier studies by the authors found that a mesh in excess of 2.0 million cells provided grid independence for the nasal cavity region (Inthavong et al, 2011a) among other studies (Golshahi et al, 2010;Lee et al, 2010;Moghadas et al, 2011), while a mesh of 1.2 million cells was sufficient for grid independence of the room with human occupant model (King Se et al, 2010). The visualization and generation of the mesh was possible on a PC computer with 32 Gb Ram, and 8 processor cores.…”
Section: Computational Geometrymentioning
confidence: 92%
“…A similar work to use such a high-resolution mesh is that of Doorly et al (2008). Earlier studies by the authors found that a mesh in excess of 2.0 million cells provided grid independence for the nasal cavity region (Inthavong et al, 2011a) among other studies (Golshahi et al, 2010;Lee et al, 2010;Moghadas et al, 2011), while a mesh of 1.2 million cells was sufficient for grid independence of the room with human occupant model (King Se et al, 2010). The visualization and generation of the mesh was possible on a PC computer with 32 Gb Ram, and 8 processor cores.…”
Section: Computational Geometrymentioning
confidence: 92%
“…We started our experimental procedure by choosing five replicas of adults (three males and two females) including the face (from chin to forehead including both cheeks), nostrils, and nasal airways to the level of upper trachea of those individuals who were used by us in recent work on deposition of nanoparticles in nasal airways of infants (Golshahi et al, 2010). In brief, MRI images of ten adults were obtained under the approval of the University of Alberta Health Research Ethics Board and the regions of interest were identified in those images based on grayscale level using the Mimics software package (Materialise, Ann Arbor, MI).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Nasal replicas have recently been developed in infants and children from 3 months to 14 years on the basis of computer tomographic scans at the University of Alberta (Storey-Bishoff et al 2008;Golshahi et al 2010Golshahi et al , 2011. The replicas were made of acrylic plastic.…”
Section: Introductionmentioning
confidence: 99%